Taxonomy and molecular systematic position of the freshwater genus Heteromeyenia (Porifera: Spongillida) with the description of a new species from Mexico. Issue 8 (17th November 2021) - Carballo, J. L.; Gómez, P.; Cruz-Barraza, J. A.; Yáñez, B.
Abstract : Heteromeyenia is an important genus of freshwater sponges characterized mainly by the presence of microscleres acanthoxeas. So far, two species are known from Mexico; H. baileyi and H. latitenta . In this paper, we redescribed H. latitenta and described the new species Heteromeyenia riojai sp. nov. from a morphological and molecular perspective. The main morphological characteristic of H. latitenta is the foraminal aperture of the gemmule, which is a prolonged tube, from which flattened cirrous appendages extend laterally; a characteristic absent in H. riojai sp. nov., which bears a short and slightly elevated foramen. The new species is distinguished by having acanthoxeas with fusiform to knobbed tips, gemmuloscleres in a single category, which are radially embedded in the theca of the gemmule. Due to the similarity in the form, size of the spicules, and geographic distribution of H. riojai sp. nov., and H. baileyi sensu Rioja, we considered that the Rioja's records must be assigned to the new species. We also aim to establish the phylogenetic relationships of the genus through nuclear-ribosomal molecular markers ITS2. Tree topology showed the Heteromeyenia species clustered together in a robust clade and closer to Corvomeyenia sp. (family Metaniidae) than to other Spongillidae genera. Our results support the previous molecular hypothesis, which strongly suggests the polyphyly of Spongillidae, even more in genera as Heteromeyenia and Trochospongilla, which displayed a large genetic distance with the other members of Spongillida. http://zoobank.org/urn:zoobank:org:pub:CC42E37B-A3A6-4AAAB285-BBC74729F8A7